Soil carbon dioxide venting through rice roots - Kirk, Guy J.D. (Plant Cell Environ, 2019)
The growth of rice in submerged soils depends on its ability to form continuous gas channels—aerenchyma—through which oxygen (O(2)) diffuses from the shoots to aerate the roots. Less well understood is the extent to which aerenchyma permits venting of respiratory carbon dioxide (CO(2)) in the opposite direction. Large, potentially toxic concentrations of dissolved CO(2) develop in submerged rice soils. We show using X‐ray computed tomography and image‐based mathematical modelling that CO(2) venting through rice roots is far greater than thought hitherto. We found rates of venting equivalent to a third of the daily CO(2) fixation in photosynthesis. Without this venting through the roots, the concentrations of CO(2) and associated bicarbonate (HCO(3) (−)) in root cells would have been well above levels known to be toxic to roots. Removal of CO(2) and hence carbonic acid (H(2)CO(3)) from the soil was sufficient to increase the pH in the rhizosphere close to the roots by 0.7 units, which is sufficient to solubilize or immobilize various nutrients and toxicants. A sensitivity analysis of the model showed that such changes are expected for a wide range of plant and soil conditions.